Role of Blockchain technology in Academic libraries: Safeguarding the Knowledge - Poologanathan, P. (Bharathidasan University, 2025)
This study examines how blockchain technology contributes to the safeguarding of knowledge in academic libraries. In the modern era, libraries employ various advanced technologies to manage vast collections, ensure operational efficiency, and meet the evolving expectations of users. Among these technologies, blockchain stands out as a significant innovation. Blockchain is defined as a decentralized, distributed ledger system that records transactions across a network of computers in a secure, transparent, and tamper-proof manner. In the academic libraries, Blockchain's immutable ledger revolutionizes digital preservation by ensuring the integrity and authenticity of scholarly resources, and by storing records on a decentralized network, academic libraries mitigate risks associated with data loss, corruption, or unauthorized modifications. Despite its promising applications, blockchain adoption in academic libraries faces many challenges such as high implementation costs, energy consumption, and the need for technical expertise. Therefore, main purpose of this study examines the role of blockchain integration to safeguarding the knowledge in the academic libraries in the digital age. Furthermore, this study emphasizes the importance of adopting blockchain as a strategic tool for future-proofing library operations, addressing evolving user expectations, and maintaining relevance in the digital age. By integrating blockchain technology, academic libraries can not only safeguard the authenticity of their knowledge repositories but also enhance operational efficiency and resilience. The findings of this study contribute to the growing discourse on the application of emerging technologies in library and information science, providing a foundation for further research and practical implementation.
Keywords: Blockchain technology; Academic library; Library collection; Digital age; Knowledge